Chemical Composition of the Same Brazilian Prop lis Sample Analyzed in 1997 and in 2012: No Freezing Effect - Conti, Bruno Jose [UNESP]; Bankova, Vassya; Sforcin, Jose Mauricio [UNESP] (Natural Products Inc, 2015)
The same propolis sample that was analyzed by GC-MS in 1997 and 2012 was examined again after being frozen for 15 years. No qualitative changes were seen in its composition; artepilin C, prenyl-p-coumaric acid, dihydrocinnamic acid, caffeic acid were the major compounds.
Keywords: Propolis; Phenolics Compounds; Gas Chromatography-Mass Spectrometry